2022
DOI: 10.1037/spy0000280
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate athlete mental health: Comparing treatment-seeking student-athletes and nonathletes on service utilization, clinical presentation, and outcomes.

Abstract: This study informs the limited findings on student-athlete mental health by comparing student-athletes and nonathletes receiving psychological services at University Counseling Centers (UCCs) on (a) UCC utilization rates, (b) clinical presentations and historical treatment experience, and (c) treatment outcomes. Method: Using naturalistic data from a large practice-research network (PRN) spanning 2017-2019, the following analyses were conducted: paired t-tests to examine UCC utilization rates in aggregate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For freshmen female swimmers (n = 5), high AI may negatively impact psychological well-being and lead to adverse coping methods (e.g., crying every day; Giacobbi et al, 2004). Across the board, studentathletes may face additional challenges with their mental health (Kilcullen et al, 2022). A strong AI can also be a large source of stress for the student-athlete.…”
Section: Athletic Identity and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For freshmen female swimmers (n = 5), high AI may negatively impact psychological well-being and lead to adverse coping methods (e.g., crying every day; Giacobbi et al, 2004). Across the board, studentathletes may face additional challenges with their mental health (Kilcullen et al, 2022). A strong AI can also be a large source of stress for the student-athlete.…”
Section: Athletic Identity and Stressmentioning
confidence: 99%
“…Furthermore, researchers have suggested that overidentification with AI can lead to destructive behaviors such as anxiety when not exercising, disordered eating, and substance use (Heird & Steinfeldt, 2013). Yet, interventions (e.g., mental skills training and/or clinical mental health counseling) for addressing mental health concerns in student-athlete populations are effective in managing symptoms of anxiety (Fogaca, 2021), burnout and sport satisfaction (Gabana et al, 2017), and overall mental health (Kilcullen et al, 2022).…”
Section: Athletic Identity and Stressmentioning
confidence: 99%